2019
DOI: 10.1002/fsn3.1100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antioxidant effect of two tripeptides isolated from fermented grains (Jiupei) and the antioxidative interaction with 4‐methylguaiacol, 4‐ethylguaiacol, and vanillin

Abstract: Jiupei (fermented grains) is the raw material for Baijiu distillation. The antioxidant activities of peptides Val‐Asn‐Pro (VNP) and Tyr‐Gly‐Asp (YGD) identified from Jiupei were evaluated according to in vitro chemical assays (e.g., 2,2′‐azino‐bis (3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt, 1,1‐diphenyl‐2‐picrylhydrazyl, and oxygen radical absorbance capacity) and 2,2′‐azobis (2‐methylpropionamide)‐dihydrochloride‐activated HepG2 cell model. The interaction on antioxidant activities between pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…The SOD catalyzes the decomposition of superoxide anions into oxygen and H 2 O 2 . The CAT and the GPx can decompose excess peroxides, preventing its transformation into more active substances, such as hydroxyl radicals, which accelerate cellular decline (Jiang et al., 2019). Cells have signal transduction pathways that sense the oxidative stress (ROS) and activate the defense genes through the transcription factor Nrf2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOD catalyzes the decomposition of superoxide anions into oxygen and H 2 O 2 . The CAT and the GPx can decompose excess peroxides, preventing its transformation into more active substances, such as hydroxyl radicals, which accelerate cellular decline (Jiang et al., 2019). Cells have signal transduction pathways that sense the oxidative stress (ROS) and activate the defense genes through the transcription factor Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…The SOD catalyzes the decomposition of superoxide anions into oxygen and H 2 O 2 . The CAT and the GPx can decompose excess peroxides, preventing its transformation into more active substances, such as hydroxyl radicals, which accelerate cellular decline (Jiang et al, 2019). and in their liver than the BD group, which can be associated with the fact that changes in the fatty acids profiles of diets (the higher saturated acids and cholesterol content in Chol+F, as well as its lower unsaturated acids content) could induce a change in the composition of fatty acids constituting the plasma membranes and the circulating lipoproteins, hence diminishing the lipid oxidation susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“… ( Girgih et al., 2013 ) Jiupei (fermented grains) Jiupei proteins Chemical/physical (ultrasounds) Hydrolysate and 2 fractions (UF): 2 Tripeptides: VNP in E1 and YGD in D1. Jiang et al. (2019) MW ​> ​5 ​kDa and MW ​< ​5 ​kDa.…”
Section: Production and Identification Of Antioxidant Bioactive Peptides From Plant Biomassmentioning
confidence: 97%
“…Another way to obtain antioxidant peptides by protein hydrolysis, which is not widely reported, was the fermentation by different bacteria ( Amadou et al., 2013 ; Coda et al., 2012 ; He et al., 2012 ; Zheng et al., 2012 ). Other methods such as ultrasonic-assisted hydrolysis ( Jiang et al., 2019 ), in combination with enzymes ( Yu et al., 2012 ), or for the pretreatment of biomass proteins ( Wen et al., 2018 , 2019 ), have been tested, but with less attention. However, it has been found that the ultrasound treatment could significantly improve antioxidant activities of the hydrolysate, likely by affecting the protein structure and increasing their susceptibility to proteolysis.…”
Section: Production and Identification Of Antioxidant Bioactive Peptides From Plant Biomassmentioning
confidence: 99%
See 1 more Smart Citation